The cultural politics of emotion - Ahmed, Sara (Edinburgh University Press, 2014)
This is a bold take on the crucial role of emotion in politics. Emotions work to define who we are as well as shape what we do and this is no more powerfully at play than in the world of politics. Ahmed considers how emotions keep us invested in relationships of power, and also shows how this use of emotion could be crucial to feminist and queer political movements. Debates on international terrorism, asylum and migration, as well as reconciliation and reparation are explored through topical case studies. In this textbook the difficult issues are confronted head on. New for this edition: a substantial 15,000-word Afterword on 'Emotions and Their Objects' which provides an original contribution to the burgeoning field of affect studies; a revised Bibliography; and updated throughout.
Keywords: approches et analyses; capitalisme; corps; discipline; féminisme; histoire et politique; militance; philosophie; queer; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques; émotions; études culturelles

LGBT activism and the making of Europe: A rainbow Europe - Ayoub, Phillip; Paternotte, David (Palgrave Macmillan, 2014)
Europe has long been regarded as a unique place for the promotion and furthering of LGBT rights. This important and compelling study investigates the alleged uniqueness and its ties to a relatively long history of LGBT and queer movements in the region. Contributors argue that LGBT movements were inspired by specific ideas about European democratic values and a responsibility towards human rights, and that they sought to realize these on the ground through activism, often crossing borders to foster a wider movement. In making this argument, they discuss the 'idea of Europe' as it relates to LGBT rights, the history of European LGBT movements, the role of European institutions in adopting LGBT policies, and the construction of European 'others' in this process.
Keywords: LGBTQIA2+; activisme; approches et analyses; cours; discipline; europe; histoire; histoire et politique; identités LGBTQIA2+; justice sociale; militance; mouvements de libération; mouvements lgbtia2+; premier cycle; queer; ressource en ligne; régions géographiques; sciences humaines; sex1183; thématiques

Quelle place pour les femmes trans au sein des mouvements féministes ? / Excluded. Making Feminist and Queer Movements More Inclusive, de Julia Serano, Seal Press, 338 p. - Baril, Alexandre (Spirale : arts • lettres • sciences humaines, 2014)
Un article de la revue Spirale, diffusée par la plateforme Érudit.
Publisher: Spirale magazine culturel inc. L'article est disponible à ce lien https://www.erudit.org/fr/revues/spirale/2014-n247-spirale01137/71100ac/
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme inclusif; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; terf; thématiques; transféminisme; transphobie; études trans*

Bisexual, pansexual, queer: Non-binary identities and the sexual borderlands - Callis, April Scarlette (Sexualities, 2014)
This article focuses on sexualities in the USA that exist within the border between heterosexuality and homosexuality. I first examine the usefulness of applying borderland theory to non-gay/non-straight sexualities such as queer and bisexual. I then give an ethnographic analysis of sexual self-identities on the borders, shedding light on how participants envisioned labels such as ‘pansexual,’ and ‘heteroflexible.’ Finally, I explore the ways that the sexual borderlands became tangible in Lexington, Kentucky at certain events and locations. Throughout, I highlight the ways that the sexual borderland touches on all sexualities, as individuals knowingly cross, inhabit, or bolster sexual identity borders.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amériques; anthropologie; approches et analyses; discipline; identités LGBTQIA2+; périodes historiques; queer; ressource en ligne; régions géographiques; sciences humaines; sexologie; sexualité; thématiques; états-unis; étude qualitative

Les représentations de figures genderqueers en art actuel : identités et sexualités : lieux de subjectivités dissidentes - Dubois, Anne-Marie (Université du Québec à Montréal, 2014)
La volonté de ce projet de maîtrise consiste à analyser la manière dont les représentations de figures genderqueers en art actuel participent à une réflexion critique des notions d'identité et de sexualité comme lieux privilégiés de résistance à l'hétéronormativité. Je souhaite démontrer à quel point la représentation du corps queerisé peut agir comme espace stratégique d'une repolitisation de la sexualité et de l'identité et ainsi contribuer à une micropolitique de résistance. Par le truchement des politiques et théories queers et féministes, les pratiques artistiques polymorphes de J.J. Levine, Dorothée Smith, Nina Arsenault et Virginie Jourdain questionnent et critiquent l'hétéronormativité et ses discours pour en dévoiler les principaux axiomes idéologiques et ainsi en déconstruire l'apparente naturalité. Dans l'objectif de comprendre et d'articuler les enjeux que sous-tendent les théories féministes et queers actuelles, je vais m'attarder plus spécifiquement à en circonscrire les prémisses enracinées dans le contexte postmoderne. En revisitant des auteurs clés tels Michel Foucault et Judith Butler, je souhaite mettre en lumière leurs contributions intellectuelles et théoriques pour la constitution d'une pensée critique des identités et des sexualités. Les représentations de figures genderqueers en art actuel participent ainsi d'une déconstruction des présupposés immanents de l'hétéronormativité dont le genre est en quelque sorte l'ancrage ontologique. En jouant de ces codes hégémoniques de manière à en désamorcer la violence symbolique, Smith, Levine, Jourdain et Arsenault participent à une remise en cause des concepts même d'identité et de sexualité pour nous faire entrevoir de possibles subjectivations dissidentes. À la source de mes réflexions, il y a ainsi une volonté épistémologique de produire un savoir mutant, progéniture androgyne d'une multitude de penseurs qui n'ont de cesse de nourrir la discipline de l'histoire de l'art. Ce mémoire est donc le mariage polygame de méthodologies hétéroclites dont l'objectif ultime est la production d'un savoir queer riche et sensible. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : postmodernisme, queer, identités, sexualités, genderqueer, J.J. Levine, Dorothée Smith, Virginie Jourdain, Nina Arsenault, micropolitique de résistance, subjectivités dissidentes, hétérotopies identitaires, hétéronormativité, pharmacopornographie.
Keywords: 1900-1999; IREF; amériques; approches et analyses; canada; discipline; europe; france; féminisme postmoderne; histoire de l'art; hétérosexisme; identités LGBTQIA2+; mémoires/thèses; périodes historiques; queer; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; épistémologie

Queering borders: Language, sexuality and migration - Murray, David A.B. (Journal of Language and Sexuality, 2014)
Preface to the special issue on queering borders in the journal of language and sexuality.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; canada; cours; discipline; histoire et politique; identités LGBTQIA2+; migration; migrations queer; premier cycle; queer; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques

Sexualité - Weeks, Jeffrey; Mendès-Leite, Rommel; Collomb-Boureau, Colette; Millet, Baudoin; Baudry, Samuel (Presses universitaires de Lyon, 2014)
Première traduction française d’un ouvrage de Jeffrey Weeks, ce « manifeste intellectuel » est d’ores et déjà un classique anglo-saxon depuis plus de vingt ans. Dès sa première édition, il s’est imposé comme une introduction de pointe aux débats sur les sexualités, le genre et l’intime. Jeffrey Weeks retrace l’histoire de la sexualité, pensée comme une construction sociale, façonnée et remodelée inlassablement par le contexte dans lequel elle existe et s’exprime : la sexualité n’est ni naturelle ni uniforme, mais culturelle et plurielle. Cette approche pionnière permet de couvrir un large champ d’investigation : les traditions religieuses, les politiques identitaires, la mondialisation, l’impact social du sida, l’influence de la génétique et de la psychanalyse, la lutte des sexes, les nouveaux modèles familiaux... Désormais, dans sa troisième édition (qui fait l’objet de cette traduction), cet essai majeur intègre de nouveaux concepts et enjeux, issus en particulier des mouvements LGBT et des débats sur le mariage homosexuel.
Section: 1 vol. (303 p.) : couv. ill. en coul. ; 18 cm.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; histoire; histoire et politique; hétérosexisme; patriarcat; premier cycle; queer; sciences humaines; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques

Queer excursions: retheorizing binaries in language, gender, and sexuality - Zimman, Lal; Davis, Jenny L.; Raclaw, Joshua (Oxford University Press, 2014)
Across scholarship on gender and sexuality, binaries like female versus male and gay versus straight have been problematized as symbols of the stigmatization and erasure of non-normative subjects and practices. The chapters of Queer Excursions offer a series of distinct perspectives on these binaries as well as on a number of other, less immediately apparent dichotomies that nevertheless permeate the gendered and sexual lives of speakers in various contexts. Some chapters focus on the limiting or misleading qualities of binaristic analyses, while others suggest that binaries are a crucial component of social meaning within particular communities of study. Rather than simply accepting binary structures as inevitable, or discarding them from our analyses entirely based on their oppressive or reductionary qualities, this volume advocates for a retheorization of the binary that affords more complex and contextually grounded engagement with speakers’ own orientations to dichotomous systems. It is from this perspective that contributors identify a number of diverging conceptualizations of binaries—including those that are non-mutually exclusive, those that liberate in the same moment that they constrain, those that are imposed implicitly by researchers, and those that recontextualize familiar divisions with innovative meanings. With each chapter having a perspective on locally salient linguistic practices that help constitute gender and sexuality in marginalized communities, what the contributions to Queer Excursions together demonstrate is that researchers must be careful to avoid the assumption that our own preconceptions about binary social structures will be shared by the communities we study.
Donné en lecture au cours LIN2685 et POL4105, Jenny L. Davis, “More Than Just ‘Gay Indians’”: Intersecting Articulations of Two-Spirit Gender, Sexuality, and Indigenousness, pp62-80.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; pol4105; premier cycle; queer; ressource en ligne; sciences humaines; sociolinguistique; sofia; thématiques